2014
DOI: 10.1002/adfm.201303941
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Disorder in Squaraine–C60 Organic Solar Cells: A Theoretical Description of Molecular Packing and Electronic Coupling at the Donor–Acceptor Interface

Abstract: 1 www.MaterialsViews.com wileyonlinelibrary.com design, processing procedures, and new device architectures. [9][10][11][12][13][14][15][16][17][18][19][20] Although these results are encouraging, there remains limited comprehensive understanding of the factors impacting the underlying physical processes that take place in OPV, and in particular how the myriad morphologies available in the active layer infl uence the fi nal PCEs.Large absorption coeffi cients, especially in the red and near-infrared spectral r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 55 publications
(115 reference statements)
1
46
0
Order By: Relevance
“…25 It has been shown in polymer:fullerene BHJs and bilayer small-molecule/fullerene devices that increased crystallinity 15 of the active layer correlates with a shift in E CT to lower energies, in agreement with our findings for C 60 and ZCl. 46 Additionally, it has been suggested that steric effects at the D/A interface can increase the energy of the CT state by increasing separation between the donor and acceptor, resulting in a higher V OC . 40 Differing molecular orientation will similarly lead to changes in the electronic coupling between the donor and acceptor as different conformations may exist at the donor/acceptor interface.…”
Section: Resultsmentioning
confidence: 99%
“…25 It has been shown in polymer:fullerene BHJs and bilayer small-molecule/fullerene devices that increased crystallinity 15 of the active layer correlates with a shift in E CT to lower energies, in agreement with our findings for C 60 and ZCl. 46 Additionally, it has been suggested that steric effects at the D/A interface can increase the energy of the CT state by increasing separation between the donor and acceptor, resulting in a higher V OC . 40 Differing molecular orientation will similarly lead to changes in the electronic coupling between the donor and acceptor as different conformations may exist at the donor/acceptor interface.…”
Section: Resultsmentioning
confidence: 99%
“…Although there is increasing interest in the mechanical properties of BHJ active layers, [1][2][3][4][5][6][7][8][9] and such studies are common for traditional polymers, [10][11] the efforts in the OPV arena remain limited when compared to performance efficiency studies. [12][13][14][15][16] Along with the electronic processes involved in photocurrent generation, the active-layer mechanical properties inherently depend on the multiphase morphology of the BHJ thin films [17][18][19][20][21][22] and therefore are contingent on the thin-film processing protocols and the nature and strength of non-covalent, solid-state intermolecular interactions. However, a molecular-scale understanding of these properties, which is key to the design of more mechanically and electronically robust active layers, remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Their simulations indicate that even at 300K, the thermal motions of the molecules at the interface can be quite profound and the degree of disorder inherent around the interface can greatly affect the formation of electron/hole pairs. 28 Finally, we recently presented a fully quantum dynamical model of photo-induced charge-fission at a polymeric type-II heterojunction interface. 29 Our model supposes that the energy level fluctuations due to bulk atomic motions create resonant conditions for coherent separation of electrons and holes via longrange tunnelling.…”
Section: Introductionmentioning
confidence: 99%